An electron holography study of perpendicular magnetic tunnel junctions nanostructured by deposition on pre-patterned conducting pillars. Issue 33 (13th August 2020) - Boureau, V.; Nguyen, V. D.; Masseboeuf, A.; Palomino, A.; Gautier, E.; Chatterjee, J.; Lequeux, S.; Auffret, S.; Vila, L.; Sousa, R.; Prejbeanu, L.; Cooper, D.; et al.
Abstract : Electron holography investigation of the magnetic induction field of perpendicular magnetic tunnel junctions for the fabrication of magnetic random access memories (MRAM), and temperature behavior. Abstract : The fabrication of multi-gigabit magnetic random access memory (MRAM) chips requires the patterning of magnetic tunnel junctions at very small dimensions (sub-30 nm) and a very dense pitch. This remains a challenge due to the difficulty in etching magnetic tunnel junction stacks. We previously proposed a strategy to circumvent this problem by depositing the magnetic tunnel junction material on prepatterned metallic pillars, resulting in the junction being naturally shaped during deposition. Upon electrical contact, the deposit on top of the pillars constitutes the magnetic storage element of the memory cell. However, in this process, the magnetic material is also deposited in the trenches between the pillars that might affect the memory cell behaviour. Here we study the magnetic interactions between the deposit on top of the pillars and in the trenches by electron holography, at room temperature and up to 325 °C. Supported by models, we show that the additional material in the trenches is not perturbing the working principle of the memory chip and can even play the role of a flux absorber which reduces the crosstalk between neighboring dots. Besides, in the studied sample, the magnetization of the 1.4 nm thick storage layer of the dots is found to switch from out-of-plane to an in-plane configuration above 125 °C, but gradually decreases with temperature. Electron holography is shown to constitute a very efficient tool for characterizing the micromagnetic configuration of the storage layer in MRAM cells.